Frequency and pattern of respiratory diseases in children - Samoo, Urooj; Ehsan, Shaista; Agha, Farah (International Journal of Contemporary Pediatrics, 2017)
Background: Respiratory tract infections are a major cause of morbidity and mortality in children. Therefore, it is imperative that research studies be conducted to determine the pattern of respiratory diseases in the pediatric age group. Present study was done to determine the outcome, frequency and pattern of respiratory infections in children admitted in a tertiary care hospital. Methods: This prospective, cross-sectional study was conducted from September 2014 to February 2016. Data was analyzed on SPSS 20.0. P value of <0.05 was observed noteworthy. Results: A total of 286 children were admitted with respiratory diseases. Out of these there were 180 cases of Pneumonia. Peak occurrence of Pneumonia was observed in first trimester of the year. Conclusions: Efforts are required to devise strategies to decrease the burden of respiratory diseases in children.